Pendekatan Kognitif dalam Teori Kesehatan Mental Al-Balkhi: Psikologi Positif di Abad Keemasan Islam - Naufil Istikhari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
This research is to present a ninth-century Muslim polymath, Abu Zayd Al-Balkhi, and his theoretical contribution on the formation of the epistemological equilibrium between mental disorder and mental health which tends to be separated in the history of Western psychology. In his phenomenal treatise, The Sustenance of Body and Soul, Al-Balkhi made a bridge between ‘positive’ and ‘negative’ psychology in the common clinical approaches. This study also reveals the cognitive therapy approach as Al-Balkhi’s authentic finding in the Islamic world, an approach well known long before modern psychology developed. Particular attention is paid to Al-Balkhi’s emphasizes in positioning his theory of mental health, especially in a positive approach, in such as a pioneer of the Western psychological one.